Analisis Pengembangan Keterampilan Mengajar dan Dampaknya Pada Kinerja Guru di SD Negeri Tanjungwangi - Yanti, Risma; Soleha, Lilis Karnita (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Human resources (HR) are related to human power in the education system. Teacher human resources include qualifications, skills, knowledge, attitudes and their contribution to student development and the education system. Considering the dynamics of the world of education, teachers need to have the ability to adapt to respond to changes in curriculum, technology and developing learning methods. In the educational process, teaching and learning is the main activity, and if the teacher is interesting and has good skills then students will be interested and participate in the learning set by the teacher. Teacher performance is a learning process that occurs both outside and inside the classroom. The effectiveness and efficiency of the education system can produce strong and quality human resources. This research aims to determine the development of teaching skills and its impact on teacher performance at Tanjungwangi State Elementary School. The type of research used is a qualitative method. The results of this research show that developing teaching skills, especially those related to the application of technology in learning, is an inseparable part of efforts to improve teacher performance and the effectiveness of the learning process. The development of teaching skills impacts individual teacher performance, but also the effectiveness and overall learning experience of students. the importance of developing adaptive and technology-based teaching skills in increasing the effectiveness of learning and teacher performance.